Pengaruh Lama Penyinaran Lampu Led Merah, Biru, Kuning Terhadap Pertumbuhan Microgreen Kangkung (Ipomoea reptant) - Lizda As’adiya; Indiyah Murwani (Folium : Jurnal Ilmu Pertanian, 2021)
Microgreens are vegetables that can be harvested about 7-14 days after germinationwhich has a higher nutrient and vitamin content than commonly grown vegetables. Thisstudy aims to determine the interaction between the type of light and the duration oflighting and the effect of the types of red, blue, yellow LEDs and red, blue, yellow LEDlighting on the growth of kangkung microgreen. This research is a box experiment using aSplit Plot Experiment Design with 9 treatments and 3 replications. The results showed thatthere was an interaction between the type of lamp and the duration of lighting to thegrowth of kangkung microgreen. The combination of C3T1 treatment (Yellow LED + 6hours) produced the highest plant length, namely 6.47 cm at 7 DAS, the number of leaveswas 2.00 for all treatments. The different types of lamps in kangkung microgreen had asignificant effect on growth, where the blue LED light produced the highest number ofleaves, namely 2.00 leaves at 14 DAS. The highest fresh weight per box was 18.36 g. While the Yellow LED produced the highest plant length of 9.42 cm at 14 DAS, the highestnumber of leaves was 2.00 pieces 14 DAS, the highest root length was 7.22 cm, thehighest dry weight per box was 1.03 g. The difference in lighting time onkangkung microgreen has a significant effect on the growth, where the 6 hours lightingduration produces the highest root length, namely 7.96 cm, the highest fresh weight perbox is 23.17 g, the highest dry weight per box is 1.87 g. The length of 12 hours of lightingresulted in the highest plant length, namely 10.41 cm at 14 DAS, the highest number ofleaves was 2.00 leaf blade. Based on the results of this study it can be recommended thatthe cultivation of kangkung microgreen in the box experiment can be using lighting for 6hours and pay attention to the microelements that affect the microgreen for better growth.